Comparison of Oral Versus Intravenous Fluorescein Widefield Angiography in Ambulatory Pediatric Patients. (May 2017) - Manoharan, Niranjan; Pecen, Paula E.; Cherof, Amy M.; Oliver, Scott C. N.; Palestine, Alan G.
Purpose: To compare the image quality and clinical utility of oral versus intravenous (IV) dye administration for fluorescein widefield angiography in pediatric patients. Design: Retrospective observational case series. Methods: Retrospective chart review of pediatric patients who underwent noncontact widefield fluorescein angiography (FA; Optos plc) at a single tertiary referral center (UCHealth Eye Center, Aurora, Colorado) between January 1, 2014, and May 31, 2016. Fluorescein angiography images were de-identified, and FA timing was hidden. A masked retinal specialist graded FA image quality and clinical utility. Results: A total of 103 FAs (62 IV and 41 oral) in 82 patients were reviewed. Oral fluorescein administration was more common in young patients (mean age: 8.1 years) compared to IV administration (mean age: 14.5 years; P < .001). Multivariate analysis with adjustment for age showed no statistical difference between oral and IV FA image quality ( P = .59). There was a high incidence of excellent clinical utility in both oral and IV FAs, with no statistically significant difference between the 2 methods. Subgroup analysis of familial exudative vitreoretinopathy, Coats' disease, choroidal neovascular membrane, and uveitis also showed no statistical difference in clinical utility between IV and oral FA. Conclusion: Oral widefield FA had excellent clinical utility and comparable image quality to IV fluorescein widefield angiography (with adjustment for age). For the evaluation of pediatric retinal disease, oral FA can be a clinically useful diagnostic tool in pediatric patients who are intolerant to IV access, which may avoid some need for FA under general anesthesia.